Level of Fish Consumption and Factors Affecting the Community of Sanana District, Sula Islands Regency - Irham, Irham; Norau, Sahlan; Hi. Iksan, Kusdi; Umasangaji, Nursia (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Sanana District is a strategic center of economic movement in the Sula Islands Regency, because it is supported by the existence of a fish trading center, namely the Basanohi traditional market, but this condition has not contributed significantly to increasing fish consumption in this region.Capture fisheries production in the Sula Islands is 21.5 thousand tonnes, with a community fish consumption rate of 44.3 kg/capita/year, which is still relatively low compared to other districts/cities (BPS Sula Islands, 2020). The purpose of this study was to determine the level of fish consumption and the factors that influence fish consumption in the people of Sanana District. This study uses survey and observation methods. The data collected consists of primary data and secondary data. Sampling using simple random sampling technique. Respondents totaled 55 people/families with provisions for the distribution of each village having 5 respondents, namely the villages of Fagudu, Falahu, Fatcei, Fogi, Mangon, Pastina, Umaloya, Wai Ipa, Waibau, Waihama, and Wailau. Data analysis used analysis of Fish Consumption Rate (MMR) to determine the level of fish consumption in Sanana District. Meanwhile, to find out the factors that influence fish consumption in Sanana District using multiple linear regression analysis. The research results obtained showed that the level of fish consumption in Sanana District was 951.69 kg/month. Income factors, number of family members and education have an effect on fish consumption in Sanana District.